Research Trends in the Use of Automated Writing Evaluation Tools - Wulandari, Kurnia (Lingua Pedagogia, 2024)
This systematic review aimed to present a systematic summary of the trends and use of Automated Writing Evaluation (AWE) tools, particularly in teaching writing skills in the university context. Research articles were collected from three different databases, namely Eric, Taylor & Francis, and Scopus. After being reviewed based on selected inclusion and exclusion criteria, 21 studies out of 76 collected articles were then further examined. The findings of this study showed that the use of AWE tools increased from 2020 to 2022.  In addition, the majority of studies were conducted in China where English is learned as a second or foreign language. Then, most of the reviewed studies were developed based on the quantitative research design. Meanwhile, regarding the AWE tools, Pigai was found to be dominantly used by students, and the second most commonly used tools were Grammarly and Criterion.  At last, based on this systematic review, AWE tools were frequently used to help students to write essays.